DEVELOPMENT OF SUBSTORM CROSS-TAIL CURRENT DISRUPTION AS SEEN FROM THE GROUND - GAZEY, NGJ; LOCKWOOD, M; SMITH, PN; COLES, S; BUNTING, RJ; LESTER, M; AYLWARD, AD; YEOMAN, TK; LUHR, H (AMER GEOPHYSICAL UNION, 1995)
We discuss substorm observations made near 2100 magnetic local time (MLT) on March 7, 1991, in a collaborative study involving data from the European Incoherent Scatter radar, all-sky camera data, and magnetometer data from the Tromso Auroral Observatory, the U.K. Sub-Auroral Magnetometer Network (SAMNET) and the IMAGE magnetometer chain. We conclude that for the substorm studied a plasmoid was not pinched off until at least 10 min after onset-at the local time of the observations (2100 MLT) and that the main substorm electrojet expanded westward over this local time 14 min after onset. In the late growth phase/early expansion phase, we observed southward drifting arcs probably moving faster than the background plasma. Similar southward moving arcs in the recovery phase moved at a speed which does not appear to be significantly different from the measured plasma flow speed. We discuss these data in terms of the ''Kiruna conjecture'' and classical ''near-Earth neutral line'' paradigms, since the data show features of both models of substorm development. We suggest that longitudinal variation in behavior may reconcile the differences between the two models in the case of this substorm.